From rifting to Indosinian orogeny recorded in the Indochina from late Devonian to late Triassic: A review - Luong Thi Thu, Hoai; Nguyen Van, Vuong; Faure, Michel; Wei, Lin; Vu Tien, Thanh; Tran Thi Thanh, Nhan; Nguyen Thi Minh, Thuyet (Vietnam Journal of Earth Sciences, 2024)
The Indochina block, the most significant part of South East Asia, is bounded by the Ailaoshan-Song Ma suture zone in the north and Jinghong-Nan-Uttradit, Sra Kaeo suture in the west. These sutures result from the various tectonic events related to the rifting and closing of the Paleo-Tethys and successive collision of South China (Sino-Vietnam)-Indochina-Sukhothai arc-Sibumasu continental blocks. However, the timing of the commencement of the rifting eastern Paleo-Tethys, subduction, subsequent collision orogeny, duration of these stages, and their geodynamic mechanism remain controversial. Our review of the stratigraphic, sedimentary, magmatic, metamorphic, structural, and geochronological data available for the suture zones bounding and interior of the Indochina block indicate successive tectonic events from rifting through subduction to orogeny and provide new insights into the tectonic history from Late Devonian to Triassic that shape the Indochina block and its adjacent regions. The remnant of the Paleo-Tethys branch and deep marine cherts represented by the Ailaoshan-Song Ma and Nan-Uttaradit suture melanges record the rifting and oceanic crust formation stage at ~380-313 Ma and 316-310 Ma, respectively. The southwestward subduction of the South China block under the Indochina block resulted in the development of the magmatic arc at ~ 310-247 Ma in the north Indochina block; meanwhile, the subduction of the Sibumasu block below the Indochina gave rise to the Sukhothai magmatic arc and Jinghong-Nan-Luang Prabang-Loei back-arc basins in the western Indochina at ~278-235 Ma. The South China slab rollback may significantly affect arc magmatism distribution in the north Indochina block. The final closure of the eastern Paleo-Tethys resulted in Indosinian collision orogeny of the Indochina with South China blocks at ~250-230 Ma in the Ailaoshan-Song Ma suture, followed by the Sibumasu block with Indochina-South China continent at ~240-230 Ma in the Jinghong-Nan-Uttradit-Sra Kaeo sutures. The late to post-collisional orogeny occurred in the north and west Indochina at ~235-200 Ma and ~230-200 Ma, respectively.